Pengaruh Belanja Modal Dengan Pendapatan Asli Daerah Sebagai Variabel Intervening Terhadap Pertumbuhan Ekonomi Daerah Di Kabupaten Bengkalis - Anshor Wibowo; Monalisa Monalisa (JAS (Jurnal Akuntansi Syariah), 2019)
This research aims to determine the effect of Capital Expenditure on Economic Growth with Regional Original Income as an Intervening Variable in Bengkalis Regency. The population in this study is the report of realization of the revenue and expenditure budget of Bengkalis Regency in 2013 to 2017, Sampling is done using the purposive sampling method and the number of samples is 12 items from regional original income in 2013 to 2017, 12 items of capital expenditure in 2013 to 2017 and economic growth 2013 to 2017. This research data is in the form of secondary data in the form of 2013 to 2017 Budget Realization Report in the Regional Government Financial Statements that have been examined by the Indonesian Financial Audit Board in 2013 to 2017. The results of this study are that capital expenditure has an effect on growing the economy, whereas capital expenditure indirectly influences regional economic growth through regional original income as an intervening variable.